Long-Term Monitoring of Liver Fibrosis and Steatosis in Patients with Chronic Hepatitis C after Achieving a Sustained Virologic Response to Antiviral Therapy - K. R. Dudina; P. A. Belyy; I. V. Maev; N. Kh. Safiullina; E. A. Klimova; S. A. Shutko; O. O. Znoyko; N. D. Yushchuk (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze the dynamics of fibrosis and steatosis of the liver according to fibroelastometry in patients with chronic hep-atitis C (CHC) after ≥ 6 months from transient elastometry (TE) achieving a sustained virologic response (SVR) to antiviral therapy.Materials and methods. At baseline, a prospective observational study included 628 CHC patients with known stage of liver fibrosis (F) before AVT, some of whom were phased out due to non-compliance with the inclusion criteria. The final analysis included 297 patients who had transient elastometry (TE) data with CAP™ technology on the severity of liver fibrosis (± steatosis) before treatment and after ≥ 6 months after reaching SVR (67 % – interferonfree regimens of therapy). Median follow-up from the moment SVR was confirmed was 3 years [2; 6].Results. At the end of the study, the average age of patients was 49 ± 12 years, of which 53 % were men. In the long-term period after reaching SVR, regression of liver fibrosis was diagnosed in 80 % of cases (including in patients with cirrhosis), and the progression of fibrosis was in 3 % of patient. At the same time, regression of liver steatosis was detected only in 31 % of the patient, worsening of the results was in 23 % (26 % of them had the appearance of steatosis (S) of the liver of 1–3 degrees in persons with no fatty liver before the start of AVT). In the group of patients with liver steatosis, the proportion of men was significantly higher (p = 0.004). Clinically significant stages of fibrosis F3–F4 were significantly more often recorded in patients with hepatic steatosis, both before treatment (46 % S1–S3 and 22 % S0, p < 0.001) and after ≥ 6 months after reaching SVR (19 % S1–S3 and 9 % S0, p = 0.023).Conclusion. In patients with chronic hepatitis C with SVR achieved in the long term, despite a significant regression of liver fibrosis, a high prevalence of hepatic steatosis remains. The data obtained indicate the feasibility of routine diagnosis of both fibrosis and steatosis of the liver in the management of patients with chronic HCV infection before and after successful antiviral therapy.